2021
DOI: 10.3390/ani11030607
|View full text |Cite
|
Sign up to set email alerts
|

Carcass Composition, Meat Quality and Sensory Quality of Gentile di Puglia Light Lambs: Effects of Dietary Supplementation with Oregano and Linseed

Abstract: There is a growing demand by the modern consumer for meat containing less fat and lower levels of saturated fatty acids, which are considered to increase the risk of coronary heart disease. In southern Italy, the Gentile di Puglia breed is one of the most common on farms, and the light lambs are often consumed. The study evaluates the effect of a diet containing extruded linseed (Linum usitatissimum) on growth performances, carcass traits, and meat quality in Gentile di Puglia light lambs. Thirty-six male lamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…The CP content at 24 h and 3 d was similar; however, on days 6, 12, and 24 of storage, the inclusion of OEO increased CP values. At 24 h, the addition of OEO did not affect the chemical composition of the meat, observing similar results to those reported in the study by Scarpa et al [30] in the Longissimus lumborum muscle of lambs. Likewise, they are similar to those observed by Rivaroli et al [60] when evaluating a mixture of essential oils (oregano, garlic, lemon, rosemary, thyme, eucalyptus, and orange) in diets for calves.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The CP content at 24 h and 3 d was similar; however, on days 6, 12, and 24 of storage, the inclusion of OEO increased CP values. At 24 h, the addition of OEO did not affect the chemical composition of the meat, observing similar results to those reported in the study by Scarpa et al [30] in the Longissimus lumborum muscle of lambs. Likewise, they are similar to those observed by Rivaroli et al [60] when evaluating a mixture of essential oils (oregano, garlic, lemon, rosemary, thyme, eucalyptus, and orange) in diets for calves.…”
Section: Discussionsupporting
confidence: 90%
“…However, Sun et al [9] mentioned a positive effect on final weight, DWG, and DMI by including 300 mg kg −1 of OEO in diets for lambs and a decrease in feed conversion. In the same context, Scarpa et al [30] used a combination of flaxseed and OEO, without effect on the productive performance of lambs. The differences in the positive results when two essential oils or another compound are used can be explained by the interaction of the compounds with a synergistic effect that favors the mixture's effectiveness on the productive performance of the lambs [31].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it was reported that 250 or 500 ppm of oregano oil did not change the relative omental or mesenteric fat weights in the lambs (Demirel et al, 2013). Scarpa et al (2021) reported that the percentage of the abdominal region dropped markedly in lambs fed pelleted feed that contained 3% extruded linseed and 0.6% dried oregano (Origanum vulgare L.) inflorescences when compared to the control group. Moreover, in the present study, the back fat thickness was higher in the female lambs than in the male lambs.…”
Section: Discussionmentioning
confidence: 79%
“…In another study, the oral administration of rosemary essential oil (0.6 mL/day) to lambs substantially improved the ΣPUFA, ΣPUFA/ΣSFA, Σn-6, Σn-3, and Σn-6/Σn-3 values (Smeti et al, 2017). Scarpa et al (2021) found that the mixture of extruded linseed and dried oregano inflorescences decreased the ΣSFA and Σn-6/Σn-3 values in lamb meat, while not changing the ΣMUFA values, but increasing ΣPUFA, ΣUFA, Σn-6, and Σn-3 values. These differences can basically be attributed to the bio-hydrogenation process in the rumen.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation